Cambios paradigmáticos en educación - Juan Casassus (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2002)
The article analyses two qualitative paradigmatic changes, which are taking place in education and which are affecting the community of educators. The first occurs at the organisational level, that is, in the way of representing the context in which the education system functions. The fundamental objective is to understand current management proposals which involve the concept of quality as a reply to demands and pedagogical identity. The second takes place within the components of the curricular matrix and is expressed at the level of learning, syllabus and evaluation. In the latter case, the article argues that the conductivist matrix is giving way to a constructivist matrix. The article concludes by affirming that the paradigmatic changes ought to assume as their fundamental tenet the repositioning of the subject. This implies, on the one hand, a new understanding of how individuals come to terms and interact with other individuals. On the other, it also implies placing the subject at the centre of learning, as an active actor in the construction of knowledge.